REVIEW ARTICLE: DEVELOPEMENT AND USING DENGUE VACCINE FOR DENGUE INFECTION VIRUS - Massey, Firdaus Kabiru; Yulia, Rika (Jurnal Ilmu Kesehatan dan Kesehatan, 2019)
Abstract : Tropical and subtropical countries are regions with high incidence of dengue infection. Dengue virus infection is estimated to cause 300 million new infections in one year and approximately 1 million severe cases with 2 + 5% deaths. The case of dengue in Indonesia has continued to increase since 1968 until 1980 where all provinces in Indonesia have been affected by the dengue virus. Dengue virus is a virus carried by the Aedes aegypti mosquito in its salivary gland. The virus which is a family group of Flaviviruses has four homologous serotypes, namely DENV-1, DENV-2, DENV-3, and DENV-4, which can cause dengue infection in individuals. Currently there is a shift in the target population from children to adults. This is a problem that needs to be resolved by the government and the community itself. Solution to overcome this, the government needs early prevention efforts to reduce the severity of dengue infection by developing and researching dengue vaccines. Currently a vaccine has been found that can be used as prophylaxis for dengue virus, namely Dengvaxia. This vaccine has been recommended by the World Health Organization (WHO) as prophylaxis for dengue infection, but Dengvaxia is only used in areas that are very endemic to dengue fever. The Indonesian Food and Drug Supervisory Agency (BPOM RI) has also approved the use of Dengvaxia as an indication of prevention of dengue infection since August 31, 2016. This vaccine has been approved globally only given to individuals aged between 9-16 years.  Keyword : dengue virus, dengvaxia vaccine, Aedes aegypti, endemic